Wideband Cell-Free mmWave Massive MIMO-OFDM: Beam Squint-Aware Channel Covariance-Based Hybrid Beamforming - Femenias, Guillem; Riera-Palou, Felip (IEEE transactions on wireless communications, 2022)
This paper considers the design of beam squint-aware channel covariance-based hybrid beamformers for wideband cell-free millimeter-wave (mmWave) massive multiple-input multiple-output (MIMO)-orthogonal frequency division multiplexing (OFDM) systems. Single and double phase shifter-based analog radio frequency (RF) precoder/combiner strategies are proposed that are based on dissimilar beam squint awareness assumptions. The digital precoding/combining stage is implemented using centralized designs maximizing the signal-to-interference-plus-noise-ratio (SINR) and relying on the uplink (UL)/downlink (DL) duality enabled by the time division duplex (TDD) protocol and the use of either phase shift-aware minimum mean square error (MMSE) or phase shift-unaware linear MMSE (LMMSE) channel estimators. The performance of the proposed beam squint-aware hybrid beamforming strategies is assessed through extensive numerical simulations under different scenarios. Numerical results show that beam squint-aware designs outperform the beam squint-unaware strategies, specially in typical wideband cell free mmWave massive MIMO-OFDM scenarios where a combination of a very high carrier frequency, a large system bandwidth, and a large-scale antenna array causes the spatial-wideband effect.